PENGARUH KOMPENSASI TERHADAP MOTIVASI DAN KINERJA KARYAWAN PADA HOTEL PULLMAN JAKARTA CENTRAL PARK - Endang Sukma Rini; Bonifasius MH. Nainggolan (LPPM Universitas Asa Indonesia, 2015)
This study is purposed to analyze the performance employess of Pullman Hotel Jakarta Central Park. This study used a compensation as the independent variable in order to analyze and used motivation as an intervening variable to measure how high the influence of compensation to the employess performance. Data were collected using a questionnaire by providing a list of questions or questionnaires directly to the respondents. Data analysis techniques in this study using SEM (Structural Equation Modelling) operated through LISREL program version 8.54. The results of this study show that the compensation variable is positively influence to the motivation. Compensation variable showed unsignificant positive impact to the performance. And the motivation variable showed significant positive impact to the performance.